The Hidden Story of Jesus - O'Collins, Gerald (New blackfriars, 2008)
On Christmas Day 2007, Channel Four took its viewers for two hours on an alleged search for ‘the real Jesus’. The programme largely failed to introduce any real experts; there were errors and painful gaps in the ‘information’ provided; there was hardly any recognition that, over and over again, there was another side to the positions being presented. Among the fantasies once again trotted out was Jesus’ supposed life and death in India, a ‘thesis’ that was invented without a shred of evidence in the 1890s. The presenter repeatedly pushed theories about early followers of Jesus reworking beliefs and practices from Gnostic and other sources. St Paul was portrayed as the ‘real’ founder of Christianity, without a word being said about this view being proposed and long ago refuted. The poor quality of this programme was astounding. One expects something much better, especially on Christmas Day.